Konsep Keadilan Sosial di Era Modern Perspektif Al-Qur’an: Studi Qur'an Tematik - Vera Nungki; Muhammad Alif (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This article examines how the concept of justice is viewed from the perspective of the Qur'an through 20 selected verses, and examines its relevance to the challenges of social life in the modern era. Using a Structured Thematic Analysis (ATT) approach to systematically organize thematic patterns from the data and grounded theory to form a specific theory from the selected verse data. From the 20 verses used, this study has shown that the Qur'an builds the concept of social justice through three main pillars: (1) Principles of Justice (2) distributive justice in the management of assets (zakat, infaq, and waqf), and (3) justice procedures in law. These concepts have high relevance in addressing global social challenges such as poverty, corruption, and human rights violations. These themes are explained as reformists towards challenges and modern life such as digital deviation, rampant corruption, and discrimination based on social identity. This condition demands a comprehensive value framework as a solution, and the Qur'an as a source of universal Islamic teachings is seen as having relevant principles of justice to address these challenges. The results of this study confirm that the Qur'an has provided a comprehensive framework of justice that is relevant as an alternative solution to injustice in the present era. This proves that the Qur'an is the key to all problems, especially social justice in this modern era. The conclusion is that the Qur'an has offered a holistic and universal system of social justice values, which is not only vertical (human relations with God) but also horizontal (relationships between humans), so that it can be an ethical alternative in building a just and almost society in this modern era.